PENINGKATAN HASIL BELAJAR IPA MELALUI METODE PROBLEM BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN SERTA IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH DASAR - Saraswati, Dewi (Universitas Muria Kudus, 2017)
The purpose of this research is to know the steps and to improve student’s learning outcomes on science learning material style of fourth grade students of SD Negeri Ledok 07 by implementing ‘Problem Based Learning’ assisted by educational video. This type of research is a classroom action research that applies the ‘Problem Based Learning’ method with educational video with two cycles. Cycles I and II consist of three meetings. The subjects of the study were the fourth grade students. In first condition the average classical score is 81.4 with the total number of students who complete are 28 students and the number of students who is not complete are 7 students. In the first cycle of science learning outcomes increased to 81.6 and on the second cycle average student learning outcomes increased again to 87.6. Percentage mastery of student learning outcomes also increased. In cycle I the percentage of completeness reached 88.6% and in cycle II percentage of completeness reached 97.2%, thus it can be concluded that the PBL method with educational video can improve student learning outcomes SDN Ledok 07.